Estudo comparativo entre estruturas com ligações rígidas e flexíveis em uma passarela para pedestres de estrutura mista de aço e concreto - Andrade Junior, Antonio Carlos de (2019)
This paper approaches the design of two steel and concrete composite structures for a pedestrian bridge of identical geometry, submitted to the same loads, but with different internal bonds. One structure has rigid beam-column connections, and the other has flexible connections. The objective is to compare the obtained results, identifying the advantages and disadvantages inherent to the adoption of each type of connection in terms of structure slenderness, total weight of material used and detailing complexity. Two structures were conceived with steel columns, composite beams and composite slabs with incorporated steel decks arranged perpendicularly to the beam direction. The structures were numerically modeled using the computer software SAP2000, version 14, and the structural dimensioning of the elements was performed in accordance to the procedures described in ABNT NBR 8800:2008. By comparing the results of the dimensioning, it was observed that the structure with rigid beam-column connections presented thinner beams, but more robust columns due to the bending moment transfering, from the beam to the columns. Analyzing the total weight of material used in the two structures, it was verified that the structure with rigid beam-column connections resulted on a heavier structure, besides the higher complexity of detailing and executioning. Therefore, it was concluded that, for the structure studied in this paper, the option for rigid beam-column connections does not presents significant advantagens to the flexible option. Instead, it results in a heavier structure, of more complex connections and, consequently, higher cost.